Stocking effects on seasonal tree transpiration and ecosystem water balance in a fast-growing Eucalyptus plantation in Brazil - Hakamada, Rodrigo Eiji; Hubbard, Robert M.; Stape, Jose Luiz [UNESP]; Lima, Walter de Paula; Moreira, Gabriela Gonçalves; Ferraz, Silvio Frosini de Barros (Elsevier, 2020)
High stocking short rotation plantations provide high yields for bioenergy use and have been adopted worldwide, especially in tropical areas. This silvicultural approach might alter ecosystem water balances compared with lower stocking, longer rotation practices. The sensitivity of water balance to stocking might also differ among genotypes. We evaluated the primary components of ecosystem water balance (transpiration - Et, canopy interception - Ei, soil evaporation – Es) for two hybrid clones that differ in drought tolerance and productivity (E. urophylla × E. grandis, Clone B2 and E.grandis × E.camaldulensis, Clone C3) planted in stockings ranging from 590 to 2,950 tree ha.-1 in a tropical region in Brazil. On a monthly time step, all water balance components of the two clones were largely related to the seasonality of rainfall, where the wet season represented 73% of the total rainfall, these processes corresponded on average to 76, 75, 67 and 70% of annual canopy interception, soil evaporation, transpiration and evapotranspiration (ET), respectively. For both clones, temperature (R2 = 0.32) and precipitation (R2 > 0.76) explained evapotranspiration responses while adding stocking as a second independent variable slightly improving the model for clone B2 but no improvement was detected for clone C3. When scaling up the monthly data to yearly analyses, all water balance components responded strongly to tree stocking for both clones during the two years of measurements (1.7 to 3.7 years-old). Annual transpiration rose linearly with stocking for the clone B2, rising from 550 mm yr−1 up to 1,039 mm yr−1, corresponding to 53–100% of precipitation (P). The clone C3 showed a much weaker influence of stocking on transpiration, rising only from 550 mm yr−1 at low stocking to 650 mm yr−1 at high stocking (53–63% of P). Canopy interception rose from about 230 mm yr−1 at low stocking to 300 mm yr−1 at high stocking, with little difference between the clones, ranging from 21 to 30% of P. Evaporation from the soil decreased with increased stocking for both clones and represented an average of 20–12% of P from lowest to highest stocking. Total evapotranspiration (ET – sum of Et, Ei and Es) was about 1,000 to 1,050 mm yr−1 at low-to-moderate stockings of both clones, but the less-drought tolerant clone B2 showed substantially higher total evapotranspiration at high stocking (2,900 mm yr−1) compared to the clone C3 (2300 mm yr−1). The difference between precipitation and evapotranspiration (the overall ecosystem water balance) declined with increasing stocking, dropping below 0 at stockings higher than 1,030 tree ha−1 for both clones. High stocking in highly productive Eucalyptus plantations may be less sustainable across multiple rotations, since any deficit in the ecosystem water balance would need to come from longer-term soil water storage. Our results indicate that both genetics and tree stocking can be used as silviculture tools to manage the sustainably of short rotation forest plantations in the face of climate change.
Keywords: Canopy interception; Planted forests; Planting density; Soil evaporation; Tree spacing; Water use